Study Some Haematological And Biochemical Parameters in Patients with Renal Failure in Diyala Province - Alaa Mohammed Albayati 1, Eman Adnan Mazher2 , Marwan A.Ahmed 3 (Indian Journal of Forensic Medicine & Toxicology, 2021)
Current study was happened in Baqubah province for kidney failure patients ( in Ibn Sina Center ) fordialysis in Baqubah teaching hospital and started from September (2016) to march (2017). (100) samples ofblood collected from patients of renal failure, males number (61) and females (39) with age range (10–88)years and collected (50) samples of blood from healthy individual have been accredited as group control ,males number (25) and females (25) with age range (10–88) years . Result of current study appeared that theratio of disease rate among males (61%) than females (39%) with no significant different between groups( P>0.05). Result of biochemical parameters expressed increased levels of B.urea, and S.creatinine Forpatients when compared with control with significant different between groups (P<0.05), so uric acid wasraised For patients when compared with control but with no significance different between groups (P>0.05),either albumin and total protein parameters were lowest For patients when compared with control withsignificance different between groups (P<0.05). The hematological parameters (HB, PCV, WBC and PLT)result were noticed decreased For patients when compared with control with significance different betweengroups (P<0.05). The conclusions of our study showed the percentage of male patients are more than female,age periods (31-50 and 51-70) years have high percentage of patients, low levels of all hematologicalparameters (HB, PCV, PLT and WBCs) in patients than controls, high levels of biochemical parameters ( B.urea, S.creatinine, Uric acid) in patients than controlsm , while (Albumin and protein) were low in patientsthan controls. The aim of current study is detecting hematological and biochemical parameters changes inpatients with Renal failure in Baqubah province.